The Severity of Gastrointestinal Disorders and Autistic-Like Behaviors Could Be Associated with a Selective Humoral Response to Bovine Milk Caseins: A Case Series - Abraham, Wall-Medrano (2024)
Severe gastrointestinal symptoms (GIS) and food hypersensitivity are tightly associated in young individuals with autism spectrum disorders (ASD). Here, we explored the relationship of GIS (gastrointestinal severity index, ROMA IV criteria, Bristol scale), ASD-like behaviors (Childhood Autism Rating Scale), and certain sociodemographic/clinical traits (epidemiological survey) with serum immunoreactivity (IgG, IgA, IgE titers) towards bovine milk caseins (BMC; by ELISA) and subfractions (by immunoblotting) in thirty-one pediatric patients (~3–15 y, 77% male) with mild-to-severe GIS and ASD-like behaviors. In total, 42%, 25%, and 23% of all participants exhibited no (IgG−/IgA−), mono (IgG+/IgA−), or dual (IgG+/IgA+) immunoreactivity to BMC, respectively; the trend was significantly associated with the severity of the GIS and ASD-like behaviors, regurgitations, and self-reported allergies (OR: 1 → (1.9–3.1) → 13.5–16.0)]. No IgE+ response to BMC was found. Dual responders were α > κ > β-casein, though nonspecific reactivity to other protein fractions was also observed. The IgA+ > IgG+ but not IgE+ response to BMC (mainly α-casein) seems to be related to the severity of GIS and ASD-like behaviors, although a larger number of ASD patients are needed to draw a causal association